Odontograms of Louis XI (1423-1483), the French king, and of Charlotte de Savoie (1441-1483), his wife - Riaud, Xavier (IJRDO - Journal of Social Science and Humanities Research, 2016)
Son of Charles VII, he was born on July 3, 1423. He spent his early childhood locked up in the Château de Loches, near Tours. In 1439, he was summoned by his father to restore peace in the Languedoc area which he did brilliantly but those efforts were not rewarded by the King. Louis got angry and instigated a revolution which was immediately shattered in 1440 although immediately forgiven by his father. The fightings followed one another which gave him a great reputation in the whole of Europe. A shrewd negotiator and the head of a ferocious army, he only met success. His mother died in 1445. As he did not get along with Agnès Sorel, his father ‘s mistress, he was sent inthe Dauphiné to reorganise the province. There he met Charlotte de Savoie whom he married in 1451without his father’s approval. Unhappy, the latter sent an army which failed to convince him to see reason. Then, Louis had no choice but to flee to Burgundy where he was granted refuge by Duke Philip the Good. He stayed there for five years. In 1461, Charles VII passed away. Louis became King of France. He was crowned on August 15, 1461. In 1465, he disbanded the League of the Public Weal through the trade of separate territorial concessions. The league was a coalition of feudal nobles organized in 1465 in defiance of the centralized authority. In 1467, Charles the Bold officially became Duke of Burgundy. A great rivalry started between the two men which ended with the death of the vassal in 1477 after fierce military and political battles which testified the Monarch’s art of corruptionto the extent of completely isolating the Duke of Burgundy until the end of his life. After numerous confrontations, weddings and subtle policies, Louis XI succeeded in rallying Picardy, Burgundy, Artois and Franche-Comté to France. On August 25, 1483, suffering from cerebral hemorrhage, the « Universal Spider » died in his château de Plessis-lès-Tours